Effects of long-term dehydration on stress markers, blood parameters, and tissue morphology in the dromedary camel (Camelus dromedarius) - Ali, Mahmoud A.; Abu Damir, Hassan; Adem, Muna A.; Ali, Osman M.; Amir, Naheed; Shah, Asma A. M.; Al Muhairi, Salama S. M.; Al Abdouli, Khaled O. S.; Khawaja, Javed R.; Fagieri, Tareq A.; Adam, Abdelnasir; Elkhouly, Aboubakr A.; et al. (Frontiers in Veterinary Science, 2023)
AA, DM, planned and advised on conduct of the study, contributed and assembled all data, conceived of the study and provided general over sight of its conduct. MA, HD, OA, KA, oversaw the day-to-day running of the study (caring for and feeding the animals, collecting and delivering blood samples, measuring body weights and collecting data for analysis) and also contributed to writing the paper.NA, MAA, AS, SM, ANA, TF, performed laboratory analysis of HPLC, Radioimmunoassay technique and Colorimetric assay; oversaw quality control of the different assays. JR, AK, ZM, MJ conceived the study and over-saw its completion and contributed to writing of the manuscript and provided statistical analysis and contributed to writing of the manuscript.